2010
DOI: 10.1002/jcc.21461
|View full text |Cite
|
Sign up to set email alerts
|

Novel graph distance matrix

Abstract: We have introduced novel distance matrix for graphs, which is based on interpretation of columns of the adjacency matrix of a graph as a set of points in n-dimensional space, n being the number of vertices in the graph. Numerical values for the distances are based on the Euclidean distance between n points in n-dimensional space. In this way, we have combined the traditional representation of graphs (drawn as 2D object of no fixed geometry) with their representation in n-dimensional space, defined by a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…In the last section, we traced the origin of the expansion coefficients of the Green’s function back to Sachs graphs. In this section, we will show an alternative way to obtain the coefficients using Newton’s identities . To this end, we again begin with eq , the most general expression for the characteristic polynomial in this manuscript where p 0 = 1 by definition.…”
Section: Where Do the Coefficients In The Power Expansion Come From?mentioning
confidence: 99%
“…In the last section, we traced the origin of the expansion coefficients of the Green’s function back to Sachs graphs. In this section, we will show an alternative way to obtain the coefficients using Newton’s identities . To this end, we again begin with eq , the most general expression for the characteristic polynomial in this manuscript where p 0 = 1 by definition.…”
Section: Where Do the Coefficients In The Power Expansion Come From?mentioning
confidence: 99%
“…For zethrenes and perylenes, we should, however, be aware of the significant shortcomings of single-reference treatments, which can have drastic effects on predictions of molecular conduction, for example . Other authors have suggested that some wholesale “renormalization” of the MO results may be needed . Here, we can simply note that there is a well-defined class of benzenoids (those with fixed bonds) for which the results of pseudo-π and HL methods are likely to deviate from those of pure CC models.…”
Section: Resultsmentioning
confidence: 94%
“…This simple function defines the entire Randić current map in the case of a catafused benzenoid. Interestingly, though, Randić himself has recently advocated weighting by area, effectively converting Model R to Model CKCDA up to scaling …”
Section: Resultsmentioning
confidence: 99%
“…This index was originally defined as the sum of path distances between any two carbons in a saturated acyclic hydrocarbon. Since it's inception this index has been generalized to a variety of structures as well as used in Quantitative structureactivity relationship (QSAR) regression models [FCH01,ME05,RPNP10,YWH04]. Some indices related to Wiener's work are the first and second multiplicative Zagreb indices [GRTW75], respectively…”
Section: Introductionmentioning
confidence: 99%